Numerical simulation of concrete block masonry under compression - Mohamad, Gihad (2012)
The main goal of this work is evaluate numerical model to reproduce the compression test of concrete block prisms, through a constitutive model of materials using the theory of plasticity and compare its results with experimental tests to preview the stress, strain and failure mode of the masonry. The post peak behavior of the material under tensile followed an exponential law and, under compression, a parabolic criterion was specified for the ascendant and descendent parts of the stress diagram and the hardening parameter. The mortar was connected to the block by the interface, for which the discrete model was employed, where the cracking occurred when the normal stress exceeded the tensile strength of the material.